Feelings of Figures in Novel Notes Juang Fiersa Besari (Personality Ludwig Klages) - Faridatus Soleha (STKIP PGRI Jombang, 2020)
This study aims to describe the feelings of the characters in the novel Juang Notes by Fiersa Bersari and researchers analyze using personality theory originated by Ludwig Klages by focusing his study on the personality structure of feelings. Feeling is a process of someone accepting or rejecting something in life. This study uses a qualitative approach by using library techniques to obtain data that will produce a description of the words or sentences in the observed study. In the analysis of this research using the hermeutics technique, in the hermeutics technique there are several stages, namely reading the research object in this study in the form of a fighting journal, the second gives a mark on the data that has been obtained from the reading results, the third provides code or coding on the data that has been found, and the fourth is to analyze data that has been obtained from the object of research in accordance with the specified research focus. Novel Notes Juang by Fiersa Besari is a novel that can be used as an inspiration for readers in living life. Based on the results of the study it was found that in the Fighting Notes novel there is a feeling that is divided into inner activities and the level of clarity, inner activities in the novel in the form of fear and guilt while viewed from the level of clarity in the form of happiness, sadness and longing.